Pengaruh Pemberian PASI Terhadap Kejadian Diare Pada Bayi Di Ruang Anak Rumah Bersalin Di Perawatan Anak (RBPA) MUTIA BANJARBARU - Ermas Estiana; Agus Rahmadi; Noorhidayati Noorhidayati; STIKES Husada Borneo; Dinas Kesehatan Kabupaten Hulu Sungai Selatan (HB PRESS, 2014)
Diarrhea is a liquid stools three or more times in one day (24 hours). One cause of diarrhea in infants is the process of preparation, processing, presentation, storage infant formula who do not follow the established procedure. The purpose of this study was to determine the effect of infant formula on the incidence of diarrhea in infants in the nursery Banjarbaru. Research methods using cross sectional analytic approach. The population was mothers with infants aged 1-12 months in the perinatology room of Mutia Banjarbaru. Sampling technique with Total Sample of 40 respondents. Based on the research results of infant formula 25 responders received (62.5%) and processing techniques that are less well PASI 17 responders (68%). Respondents who had diarrhea due to provision of infant formula 18 responders (72%). By chi-square statistical test P value = 0.00 is obtained. (P ≤ 0.05). Conclusion. There is a very significant influence on the incidence of diarrhea infant formula administration in infants in the nursery perinatology room of Mutia Banjarbaru in 2013. Suggestions. Mothers are expected to pay more attention to giving infant formula during lactation with rules laid down by the health department